PENGARUH METODE DISKUSI TERHADAP HASIL BELAJAR IPA DENGAN TEMA ORGAN GERAK HEWAN DAN MANUSIA DI KELAS V MIS IKHLAASHUL’AMAL SEBAWI TAHUN PELAJARAN 2021/2022 - Mega Mega; Purniadi Putra; Rona Rona (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2025)
This research aims to explain: 1) Science learning outcomes before using the Discussion Method with the theme of animal and human movement organs in class V MIS Ikhlaashul'Amal Sebawi. 2) Science learning results after using the Discussion Method with the theme of animal and human movement organs in class V Ikhlaashul'Amal Sebawi. 3) the significant influence of the Discussion Method on science learning outcomes with the theme of animal and human movement organs in class V MIS Ikhlaashul'Amal Sebawi. The type of research used is quantitative. The population in this study were fifth grade students and the sample in this study was 30 people. Data collection tools used the Independent Simple T-test and Nonparametric t-test: Mann Whitney. The results of this research can be concluded as follows: 1) The learning outcomes of Class V MIS Ikhlaashul'Amal Sebawi students before and after using the discussion method in the experimental group were classified as "very good (A)". The increase in the average score in the experimental group was very visible during pre -test with an average score of 53.86% and during the post-test it increased, namely with an average score of 89.93% after using the discussion method. 2) Learning Results of Class V Students of MIS Ikhlaashul'Amal Sebawi Before and After Using the Discussion Method in the Control Group obtained a total score of 788 with an average of 53.53% before being given treatment (pre-test) and 1068 with an average of 71.20 % after being given treatment (post-test). Most students got grades that were classified as needing guidance (D), and there were several students who got grades that were classified as sufficient (C). 3) do not understand the material the teacher conveys. 3) The Influence of Discussion Methods on Science Learning Outcomes with the Theme of Animal and Human Movement Organs for Class V MIS Ikhlaashul'Amal Sebawi. Based on the calculation of pre-test and post-test data for the experimental group and control group as well as using the HP = (O2 – O1) – (O4 – O3) completion paradigm with a result of 17.4% in the positive category.